DETERMINING CANDIDATE SOCIAL STUDIES TEACHERS' KNOWLEDGE ABOUT BRAIN FUNCTIONS AND NEUROMYTHS - Hatice KARA; Cengiz DÖNMEZ (International Journal of Eurasia Social Sciences, 2023)
Studies in the field of neuroscience have gained speed with the development of technology. Educators also have not been indifferent to the results of neuroscience studies in the context of brain and learning and tried to combine education with various learning methods such as brain-based learning. This situation has brought many problems with it. Normally, neuromyth, which is a term of the medical area, is also used to express the wrong opinion from the misreading or misunderstanding of neuroscience studies. Three neuromyths are very common in the educational context. The most important organ that plays an active role in learning is the brain. The fact that teacher candidates also have neuromyths for learning will undoubtedly affect education and cause neuromyths to continue to exist. In this context, the aim of the research is to determine the correct knowledge and neuromyths of social studies teacher candidates about brain functions. The research was designed with the scanning model, which is one of the quantitative methods. The participants of the study were determined by criterion sampling, which is one of the purposeful samplings. In this context, the sample of the research consisted of 2nd, 3rd, and 4th-grade social studies teacher candidates. The reason for choosing this sample group is that the pre-service teachers took a course called "educational psychology" in the first grade. 126 teacher candidates participated in the research. The data were analyzed through a quantitative statistics program and descriptive statistics. Based on the research findings, it was concluded that social studies teacher candidates have many neuromyths such as brain and learning-related brain hemispheric specialization, learning styles, Omega-3 fish oils, and critical periods.